152k views
3 votes
What is the cube root of -729a9b6

2 Answers

4 votes

Answer:

-9a3b2

Explanation:

User Roken
by
4.6k points
3 votes

ANSWER


\sqrt[3]{- 729{a}^(9) {b}^(6) } = - 9 {a}^(3) {b}^(2)

EXPLANATION

We want to find the cube root of


- 729 {a}^(9) {b}^(6)

We express this symbolically as:


\sqrt[3]{- 729 {a}^(9) {b}^(6) }

The expression under the radical called the radicand.

We need to express this radical in exponential form using the property,


{x}^{ (m)/(n) } = \sqrt[n]{ {x}^(m) }

Applying this rule gives us:


\sqrt[3]{- 729 {a}^(9) {b}^(6) } = ({- 729 {a}^(9) {b}^(6)})^{ (1)/(3) }


\sqrt[3]{- 729{a}^(9) {b}^(6) } = ({- {9}^(3) {a}^(9) {b}^(6)})^{ (1)/(3) }

Recall that


({a}^(m) )^(n) = {a}^(mn)

We apply this rule on the RHS to get,


\sqrt[3]{- 729{a}^(9) {b}^(6) } = ({- {9}^{3 * { (1)/(3) } } {a}^{9 * { (1)/(3) } } {b}^{6 * { (1)/(3) } }})

This simplifies to


\sqrt[3]{- 729{a}^(9) {b}^(6) } = - 9 {a}^(3) {b}^(2)

User Asiop
by
4.4k points